Wicked problems, complexity, and mid-level leadership in higher education: an action learning research project - Ferris, Sean, author; Barone, Ryan, advisor; Poon, OiYan, committee member; Williams, Elizabeth, committee member; Johnson, Jennifer, committee member (Colorado State University. Libraries, 2023)
Public research universities in the United States face myriad problems, many of which result in inequitable outcomes and experiences for people from marginalized populations. How stakeholders understand, value, and pursue solutions within the complex organizational context of public higher education further complicates problems of inequity and injustice. Challenges of this type can be understood as wicked problems (Rittel & Webber, 1973) and the organizational setting of public higher education a complex adaptive system (Lohmann, 2006; Mandviwalla & Schuff, 2014). A significant gap exists in the scholarship informing how higher education leaders understand and pursue solutions to the wicked problems they face within the complex adaptive systems of public universities. For this research, I used action learning methodology to explore leadership with a small group of midlevel professionals from public universities working to address challenges of inequity and injustice. Through the action learning methodology, the research process catalyzed learning and impact for participants in their local settings. Together, the participants and I generated knowledge on leadership to address wicked problems in public universities and share the research experience through the participants' accounts of practice and our practitioner learning.
Keywords: adaptive leadership; equity; wicked problems; complex adaptive systems; action research; leadership